Habitats and Foraging Movements of Larvae of Molanna uniophila Vorhies (Trichoptera: Molannidae) in Pratt Lake, Michigan, USA. (31st December 2015) - Mundahl, Neal D.; Mundahl, Erik D.
Abstract : Habitats and foraging movements of larvae of Molanna uniophila Vorhies (Trichoptera: Molannidae) were studied during four summers in Pratt Lake, Michigan. Larvae lived and fed in shallow (<10 cm), sand-bottomed lake margins, where macrophyte densities ranged from 86 to 452 stems/m 2 . Average densities of larvae varied fivefold between years (2.7 versus 13.6 individuals/m 2 ), but larval densities did not vary significantly between habitat patches with low (120 stems/m 2 ) and high (360 stems/m 2 ) macrophyte densities. Larvae and their cases exhibited strong patterns of simple, linear growth. Diets of larvae were dominated by amorphous detritus, plant debris, diatoms, and filamentous algae, but midges, cladocerans, and other microscopic aquatic animals also were consumed. Larvae shifted their bodies and cases forward across the surface sediments up to 4 times/minute while foraging, moving as much as 2.5 m/hour. Movements and distances traveled while feeding increased significantly with increased water temperatures, peaking during midafternoon hours. Distances moved by feeding larvae did not differ between habitats with low versus high macrophyte densities. Larvae foraged most actively during daylight hours and did not selectively utilize macrophyte beds as partial refugia from potential predators while feeding.